The Open-Ended Approach For Optimizing Students’ Mathematical Abilities: Does It Work? (A Meta-Analysis Study) - Dewi, Niken Shofiana; Juandi, Dadang (JETL (Journal of Education, Teaching and Learning), 2024)
This study aims to analyze the potential of applying an open-ended approach to students' math skills which contains five skills namely problem-solving, reasoning and proof, representation, communication, and connection. To really know the potential for this application to be effective, statistical analysis is needed so that more objective conclusions can be obtained. Therefore, this study used quantitative as research approach using the Meta-Analysis method. The primary studies obtained were quasi-experimental studies that examined the effect of the open-ended implementation on mathematical skills with a total of 32 articles. The articles were published from 2012 to 2023 on Google Scholar database, Semantic Scholar, and direct URL. This study provides results that the treatment effect of the open-ended approach to mathematical skill has a high effect size of 1.356 and the moderator variable that affects the heterogeneity of the study is the type of mathematical skill, which is most effective on mathematical representation skill. While the level of education and learning combination did not significantly influence the heterogeneity of the effect size.